CaGdAl3O7:Eu3+ unidimensional nanostructures: Facile electrospinning synthesis, structure and luminescence. Issue 21 (1st November 2022) - Jin, Min; Li, Ning; Shao, Hong; Li, Dan; Sun, Feng; Yu, Wensheng; Dong, Xiangting
Abstract: Inorganic luminescent materials with special unidimensional morphologies have become one kind of highly promising materials in luminescence field. Here, CaGdAl3 O7 :Eu 3+ unidimensional nanostructures containing nanofibers, nanobelts and hollow nanofibers are fabricated perfectly via facile mono-axial electrospinning technology combined with subsequent oxidation procedure. The formation mechanisms of CaGdAl3 O7 :Eu 3+ unidimensional nanostructures have been put forward and a new technology of constructing the unidimensional nanostructures is given. The morphologies of nanofiber, nanobelt and hollow nanofiber can be easily modulated via regulating the components of spinning solution and spinning parameters. CaGdAl3 O7 :Eu 3+ unidimensional nanostructures are tetragonal in structure with space group of P ‾ 421 m and possess perfect unidimensional morphologies. The unidimensional nanostructures show the predominant emissions at 590 and 619 nm under 256-nm ultraviolet light excitation, which result from 5 D0 → 7 F1 and 5 D0 → 7 F2 transitions of Eu 3+ ions, respectively. The luminescence properties of the nanostructures can be adjusted by altering Eu 3+ content, calcination temperatures and morphologies of the nanostructure. In brief, this work is of great significance for follow-up investigations of melilite group aluminates luminescence nanomaterials with distinct unidimensional morphologies. Highlights: CaGdAl3 O7 :Eu 3+ one-dimensional nanostructures are first prepared via electrospinning. Various one-dimensional structures are easily obtained by tuning spinning conditions. CaGdAl3 O7 :Eu 3+ nanofiber, nanobelt and hollow nanofiber emit excellent fluorescence. Emitting color is tuned by tuning sintering temperature, morphology and Eu 3+ content. The technique is extended to prepare other aluminate one-dimensional nanostructures.